Police recruitment and positive action: The social building blocks of service - Hesketh, Ian (International journal of police science & management, 2025)
Police recruitment in England and Wales has seen a large upsurge in recent years, with a government mandate to raise officer numbers by 20,000. Alongside this request, considerable pressure remains for the police service to diversify and recruit an increasing number of officers from under-represented groups. Although there are signs that the diversity of police forces in England and Wales is increasing, there is a paucity of available information and research on how this is happening. Existing research on current positive action programmes is underdeveloped. This study considers evidence gained from 26 long-form phenomenological interviews with new policing recruits in a single police force from the north of England. The interviews were structured using social network theory, allowing in-depth exploration of how recruits socially navigated their respective recruitment journeys. The sample provided comparative data on the journey for those experiencing positive actions and those without access to these initiatives. The data gathered offer a picture of recruits’ experiences during recruitment, allowing significant insight into the levels of social support they received. Social support is a critical element of well-being and retention. Empirical findings indicate that particular police recruitment stages exist as social building blocks for policing identity. These building blocks can be unequal depending on existing social resources. This differential identity-building during pre-socialization leads to a proposal for services to consider their positive action initiatives in a different light and ensure that they lead to the development of longer-term, supportive relationships for under-represented recruits.